Electromagnetic Energy Harvesting by Spatially Varying the Magnetic Field - Gatti, Rathishchandra; Howard, Ian (Springer-Verlag, 2011)
The need for self-powering of low power electronics has accelerated the research of energy harvesters. Electromagnetic energy harvesting poses a relatively inexpensive alternative amongst other methods but has impediments like low voltage and difficulty to scale for micro size level. This study is intended to explore the possibility of increasing the voltage by spatial variation of the magnetic field. An energy harvester design similar to a microphone is considered. A novel methodology of analytically determining the spatial variation and deducing the analytical voltage expression is discussed. This is followed by development of the theoretical model and validation by experiment. The results of the study establish that the theoretical model is not only helpful in readily predicting the output characteristics of the energy harvester but also with high accuracy. This study is helpful for developing future electromagnetic energy harvesters by spatially varying the magnetic field.